WOMEN’S EMPOWERMENT THROUGH EDUCATION MANAGEMENT - Ergasheva Ozodabonu Bahodirjon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This paper explores the role of education management in promoting women’s empowerment. By examining how inclusive, gender-sensitive educational leadership and policies contribute to social, economic, and political progress for women, the study highlights the importance of integrating women into decision-making roles within education systems. The findings reveal that when women are not only educated but also actively engaged in managing and leading educational institutions, it fosters broader societal transformation and gender equality.